2021
DOI: 10.1128/spectrum.00728-21
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Flocked Swabs with a Protective Medium Increases the Recovery of Live Brucella spp. and DNA Detection

Abstract: In order to protect public and veterinary health from highly zoonotic bacteria such as members of the genus Brucella and prevent their dissemination into the environment, direct diagnostics are of utmost importance. However, in addition to the highly specific diagnostic tests, the sampling methods, time necessary for specimens to reach the laboratories, and transport conditions are important factors to consider in order to increase the sensitivity of performed tests, especially bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(47 reference statements)
1
0
0
Order By: Relevance
“…Similar to our study, recent reports have demonstrated that other aerobic, fastidious bacterial organisms like Mycoplasma species and Brucella species were preserved better without a transport medium (Ball et al, 2020; Freddi et al, 2021). On the contrary to our findings, the addition of a transport medium, such as Amies or Stuart medium, has been shown to better preserve bacterial species by inactivating toxic substances or by keeping the swab fibres moist during transport to the laboratory (Barber et al, 1998; Barry et al, 1972; Drake et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our study, recent reports have demonstrated that other aerobic, fastidious bacterial organisms like Mycoplasma species and Brucella species were preserved better without a transport medium (Ball et al, 2020; Freddi et al, 2021). On the contrary to our findings, the addition of a transport medium, such as Amies or Stuart medium, has been shown to better preserve bacterial species by inactivating toxic substances or by keeping the swab fibres moist during transport to the laboratory (Barber et al, 1998; Barry et al, 1972; Drake et al, 2005).…”
Section: Discussionsupporting
confidence: 92%